The Pragmatics of Arabic Religious Posts on Facebook: A Relevance-theoretic Account - Zaki, Mai (Research in Language, 2017)
Despite growing interest in the impact of computer-mediated communication on our lives, linguistic studies on such communication conducted in the Arabic language are scarce. Grounded in Relevance Theory, this paper seeks to fill this void by analysing the linguistic structure of Arabic religious posts on Facebook. First, I discuss communication on Facebook, treating it as a relevance-seeking process of writing or sharing posts, with the functions of ‘Like’ and ‘Share’ seen as cues for communicating propositional attitude. Second, I analyse a corpus of around 80 posts, revealing an interesting use of imperatives, interrogatives and conditionals which manipulate the interpretation of such posts between descriptive and interpretive readings. I also argue that a rigorous system of incentives is employed in such posts in order to boost their relevance. Positive, negative and challenging incentives link the textual to the visual message in an attempt to raise more cognitive effects for the readers.